Exploring the Need for a Statistical Collaboration Laboratory in a Kenyan University: Experiences, Challenges, and Opportunities - Mawora, Thomas; Otieno, Joyce; Vance, Eric A. (Promoting Statistical Practice and Collaboration in Developing Countries, 2022)
We describe the experiences, challenges, and opportunities for statistics lecturers at Maseno University in Kenya who have established a statistical collaboration laboratory or "stat lab" called the Maseno University Laboratory for Interdisciplinary Statistical Analysis (MU-LISA). We introduce the Applied Statistics program at Maseno University and what statistical consultancy services are required in Kenya. We discuss nine challenges to operating a stat lab and how those involved in MU-LISA are overcoming these challenges. We conclude with lessons learned from creating and operating a stat lab in Kenya. This chapter explores the need for a statistical collaboration laboratory or "stat lab" at Maseno University in Kenya. The exclusion of lecturers particularly from SMSAS may be due to the impression the Principal Investigators have concerning the teaching methods in SMSAS being theoretical rather than applicable and suited to current needs in statistical computing. Currently, at Maseno University, there is no defined procedure for setting up a statistical collaboration laboratory and provisioning it with needed office space and an independent physical lab of computers for teaching statistical computing short courses and workshops. There is a need for the statistics lecturers who will work in stat labs to be conversant on how to mine and clean data before they conduct an analysis. All university programs in Kenya are regulated by the Commission for Higher Education.